Pemanfaatan Ubi Jalar Putih dan Ubi Jalar Kuning Sebagai Media Alternatif Pertumbuhan Staphylococcus aureus - Sarita Diah Kusuma Arum; Didik Wahyudi (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Nutrient Agar medium is the growth mediums for Staphylococcus aureus that has been tested to grow colonies well. NA has an expensive price, so alternative media from nature-based are needed such as white-fleshed and yellow-fleshed sweet potato which are a source of carbohydrates. This research is post-test only control group design using spread plate method that aims to find the difference in Staphylococcus aureus growth ability in white-fleshed sweet potato medium, yellow-fleshed sweet potato medium, and Nutrient Agar. Staphylococcus aureus suspense was inoculated into each growth medium and then incubated at 37°C for 72 hours. The determination of characteristics and number of colonies of Staphylococcus aureus are made every 24 hours of incubation. The number of colonies of Staphylococcus aureus at 48 hours of incubation was processed using the post-hoc test as an advanced test, the results showed that there were differences in the ability of the growth media to grow Staphylococcus aureus. Yellow-fleshed sweet potato media and NA medium had the same ability, but white-fleshed sweet potato media was better at growing Staphylococcus aureus than yellow-fleshed sweet potato media.